On-line learning - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Two post-graduate courses on post-harvest topics can be followed through computer mediated distance learning. Run by the Food Security team of the UK s Natural Resources Institute, the courses cover grain storage management (PGDip/MSc.) and post harvest